Meningkatkan Kesadaran Kesehatan Mental dan Mindfulness pada Ibu Hamil: Pelatihan untuk Kesejahteraan Psikologis - Fourianalistyawati, Endang; Febriani, Zulfa; Roro Kinanthi, Melok (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Pregnancy is an important period in a woman's life that can cause physical changes, such as nausea and fatigue, as well as psychological changes such as anxiety and depression. These changes can interfere with the well-being of the pregnant mother, which also impacts on fetal development and the quality of family relationships if not properly addressed. This community service is designed to educate participants about the importance of mental health for families during pregnancy by equipping mindfulness skills. This training is expected to provide knowledge related to the importance of managing emotions and pregnancy challenges more adaptively so as to improve the well-being of pregnant women. The activity was conducted with four pregnant women, one of whom was also accompanied by her husband. This activity was carried out for two days offline. The training was packaged by combining lecture, practice, and reflection methods. The materials covered were about mental health for pregnant women and their companions, family support for pregnant women, and mindfulness. Exercise and reflection activities consisted of mindfulness breathing, mindfulness eating, body scan, mindfulness movement, and mindful communication. Results showed a significant increase in knowledge, with posttest scores averaging 82.5%, up from 65% pretest. Participants engaged well in the activities and reflected positively on their experiences, reporting tangible benefits from the training. In conclusion, this initiative effectively enhances participants' ability to navigate pregnancy challenges adaptively.